Prevalencia de la tendinitis de manguito rotador y factores de riesgo salud en pacientes de 50 a 70 años del centro de salud santa rosa en el periodo de enero a septiembre del 2020 - Andrade Pazmiño, Juan Pablo (2022)
Rotator Cuff Tendonitis is a musculoskeletal disease, which leads to rehabilitation, so it generates a high cost to the State. OBJECTIVE: To determine the Prevalence of Rotator Cuff Tendonitis and its relationship with health risk factors in patients aged 50 to 70 years at the Santa Rosa Health Center. METHODOLOGY: Corresponds to a Descriptive and applied Study, with a Quantitative approach, reporting 837 patients treated for musculoskeletal disorders, of which 68 Older Adults between 50 and 70 years old, were diagnosed with this pathology, a sample of 38 patients were analyzed and exposed to the Laser. RESULTS: the prevalence of rotator cuff tendonitis was 8.1 % per 100 patients with musculoskeletal diseases, maintaining a close relationship with certain risk factors, according to the records increases its incidence with Age, Sex, Daily Activities, Work Activities and Trauma. In addition, the implementation of the laser to Conventional Therapy, significantly reduced the number of sessions. CONCLUSIONS: Tendinopathy is among the ten most frequent pathologies referred to the physical rehabilitation service with a close relationship according to risk factors. Finally, the inclusion of the Laser leads to the reduction of implanted sessions, with a quick return to your daily routine, improving your health and at the same time reducing public spending